Critérios para o manejo da adubação nitrogenada na cultura do feijão utilizando clorofilômetro portátil - Maia, Suelen Cristina Mendonça [UNESP] (2014)
The chlorophyll meter is a device that has allowed obtaining a relative chlorophyll index (RCI) which has correlated with the chlorophyll and leaf nitrogen (N) concentrations. Thus, the determination of RCI by chlorophyll meter can be an alternative used to predict the N necessity by common bean. However, there are doubts about which leaf and N sufficiency index (NSI) are most appropriate to define the N needed by common bean crop. Thereby the aim of this study was establish the leaf diagnosis is the most appropriated to define N supply is needed by common bean, using chlorophyll indirect readings through the use of portable chlorophyll meter (Minolta SPAD-502). For both, the research was performed in two steps. In the first step were conducted two field experiments, one with each common bean cultivar (Pérola and IPR Eldorado), during rainy growing season in 2011, with the objective of establishing which was the best leaf diagnosis (first, second, and third fully expanded trifoliolate leaf from the top) to define N necessity of common bean, using portable chlorophyll meter. The experimental design was arranged in a randomized complete block design with five treatments, consisting of N rates (0, 50, 100, 150, and 200 kg ha-1) and four replications. In the second step were conducted four experiments, two with each common bean cultivar (Pérola and IPR Eldorado) during rainy and dry growing seasons in 2012, to define the NSI, calculated based on the RCI of leaves in a reference area (without N deficiency), is the most appropriate to indicate the N requirement by common bean crop. Readings taken with chlorophyll meter were done in the leaf defined in the first step that presented the best correlation index with RCI, N concentration and grain yield. In all of experiments in the second step, the experimental design was arranged in a randomized complete block design with six N managements (M1: 200 kg ha-1 ...